(untitled) (Research, Society and Development, 2022)
The study aimed to evaluate the quality of life of women who undergo breast reconstruction after mastectomy. This is an integrative review, which was carried out by surveying the Virtual Health Library and Scientific Electronic Library Online databases. Given the analysis of the data collected, applying the inclusion and exclusion criteria, the following categories were defined: Quality of life in women after mastectomy; psychological repercussions after mastectomy with breast reconstruction; repercussions for women’s physical health and functionality in the postoperative period of mastectomy with breast reconstruction. It was observed that breast reconstruction after mastectomy improves women’s quality of life, especially regarding self-image, sexuality, and reduced rates of depression and morbidity. Satisfaction rates after breast reconstruction are demonstrated through reports related to these women’s femininity. When analyzing the difficult and critical points of the whole process, such as the feeling of mutilation and the trauma caused by the removal of the breasts, breast reconstruction can present excellent results.